Совершенствование системы пожарной безопасности в сельской местности на основе изменения структуры парка пожарных аварийно-спасательных автомобилей - Arkhipets, Николай (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
The article deals with the model of improving of the fire and rescue engines station in the rural area. The author touches upon the problem of creating of fire engines reserves.